Complementary hydrogen bonding interaction triggered co-assembly of an amphiphilic peptide and an anti-tumor drug. Issue 32 (23rd March 2015) - Cheng, Hong; Cheng, Yin-Jia; Bhasin, Sushant; Zhu, Jing-Yi; Xu, Xiao-Ding; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract : A new tumor-targeting amphiphilic peptide was designed to load and release the anti-tumor drug methotrexate (MTX), leading to reversible self-assembled morphology transition from spherical micelles to nanofibers. Abstract : We report a new tumor-targeting amphiphilic peptide that can form complementary hydrogen bonds with anti-tumor drug methotrexate (MTX), leading to reversible self-assembled morphology transition from loose micelles to densely packed nanorods or nanofibers. The MTX loaded nanorods can target tumor cells and show more than 2-fold higher cytotoxicity (IC50 = 0.38 mg L −1 ) than that towards normal cells (IC50 = 0.89 mg L −1 ).